PHARMACOGNOSTIC STUDIES ON TALINUM PORTULACIFOLIUM (FORSSK.) ASCH. EX SCHWEINF. - K, Hemalatha; P, Abirami (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study was undertaken to establish the micromorphological characters of Talinum portulacifolium (Forssk.) Asch. ex Schweinf. belonging to the family Portulacaceae. Methods: The fresh plant parts were selected for micromorphological studies, and the air-dried plant powder was used for powder analysis as per the standard techniques [1-3]. Results: Results revealed the presence of diagnostic characters like calcium oxalate crystals in the parenchyma cells of the leaf, which are druses with spiny surface that occurs in ordinary parenchyma cells. Stomata are paracytic which are present in both adaxial and abaxial surfaces of the leaf. The powder contains fragments of leaf epidermis, densely distributed stomata in laminar portions of the leaf. Conclusion: The present study provides the valuable information and also acts as pharmacognostical standards to standardize the study plant scientifically.